Preparation method of polycarbosilane composite coating for radar radome

Through the modification of polycarbosilane and resin and the coordination of inorganic fillers, a composite coating was prepared, which solved the problem of low bonding strength between the anti-laser ablation coating and the shell material, and achieved efficient laser protection and protected the aircraft Free from laser heat damage.

CN119177058AInactive Publication Date: 2024-12-24JIANGXI XINDA HANGKE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411473979.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anti-laser ablation coating has low strength and is single in performance, making it difficult to effectively protect the aircraft from the thermal damage effect of strong lasers.

Method used

Modification treatment of polycarbosilane and resin, combined with leveling agent, plasticizer and inorganic filler, the composite coating is prepared by impregnation method, and multi-stage thermal curing treatment is carried out in a protective atmosphere to improve the coating and shell material The bonding strength and anti-laser properties.

Benefits of technology

It achieves high bonding strength between the coating and the shell material and excellent anti-laser ablation performance, effectively protects the shells such as engines and missiles from laser damage, and has good thermal insulation and protection effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a polycarbosilane composite coating for a radar radome, which comprises the following steps: step 1, pretreating a to-be-coated product, coarsening the to-be-coated product by using abrasive paper or acid corrosion, cleaning the to-be-coated product by using a cleaning solvent, and drying the to-be-coated product in a drying oven, and step 2, carrying out modification treatment on polycarbosilane and resin; 3, adding a flatting agent and a plasticizer into the modified polycarbosilane, and uniformly stirring to prepare a coating solution; 4, adding an inorganic filler and a solvent into the coating solution, and carrying out rapid ball milling to prepare a mixed coating; and 5, preparing a coating on the surface of the antenna housing by adopting an impregnation method, and putting the coating into a drying oven to be cured. Polycarbosilane is converted into SiC at high temperature, epoxy resin ablates and absorbs a part of heat of laser, the contained chopped fibers and inorganic filler can play a role in heat insulation and protection, and the generated SiC and filler can reflect laser, so that the shell has excellent laser ablation resistance, and the shell is effectively prevented from being damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a surface coating, in particular to a method for preparing a surface coating of a ceramic material for a radar antenna cover. Background Art

[0002] In recent years, solid laser technology has developed rapidly, and weapons that use direct laser irradiation to kill targets are called laser weapons. Laser weapons have the characteristics of high propagation speed, fast transfer of firepower, no recoil, high firing accuracy, great killing power, and strong anti-interference ability, making them a deadly killer of various types of weapons such as aircraft. As high-energy laser weapons gradually enter the actual combat application stage, research on laser protection technology has attracted much attention. Coating materials are the most traditional form of materials for aircraft protection and realization of special functions. Since they can be constructed using simple air spraying or brushing processes, they are one of the most suitable protective materials with the lowest application cost. However, since the coating materials against lasers have extremely high requirements for material properties, research on laser protective coating materials technology is a brand new field both at home and abroad. The radiation of strong lasers to aircraft increases the temperature of the aircraft's load-bearing components, resulting in a decrease in tensile and compressive strength, thereby reducing the structural strength of the aircraft and causing it to be destroyed under its own stress. This is currently the most important strong laser thermal damage effect. See (Li Jing, Zhang Jindong, Zhang Yuzhong, Guan Zhenwei, Wang Zhiyong, Zhao Yan, Ding Heyan. Preparation and performance characterization of high temperature resistant and laser ablation resistant coatings [J]. Journal of Aeronautical Materials, 2014, 34(01): 34-38.).

[0003] The application of polycarbosilane (PCS) in the field of laser protection is mainly to absorb laser energy as a precursor and then decompose into SiC ceramics. SiC is a semiconductor ceramic material with high conductivity and good light reflectivity. It has been used in laser and far-infrared reflective screens. See (Tao Jie, Cheng Han, Chen Zhaofeng, Fang Dan, Zhang Ying. Study on the anti-laser ablation of polycarbosilane composite coating [J]. Aerospace Materials and Technology, 2008 (02): 39-42.).

[0004] At present, the damage of laser weapons is reduced mainly through structural design, anti-laser ablation coating technology, shell coating, interference technology and other means. However, among these technologies, the coating technology of anti-laser ablation coating technology is simple and low in cost. However, the bonding strength between the anti-laser ablation coating and the shell material is not high and the performance is single. The modification between polycarbosilane and resin can effectively improve the bonding strength between the coating and the shell material, and improve the performance of polycarbosilane and resin. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a polycarbosilane composite coating for a radar antenna cover, comprising the following steps:

[0006] Step 1: Pre-treat the product to be coated, roughen it with sandpaper or acid corrosion, then clean it with a cleaning solvent and put it in an oven to dry.

[0007] Step 2: Modification of polycarbosilane and resin;

[0008] Step 3: Add the modified polycarbosilane to the leveling agent and the plasticizer and stir evenly to prepare a coating solution;

[0009] Step 4: Adding inorganic fillers and solvents to the coating solution to prepare a mixed coating by rapid ball milling;

[0010] Step 5: A coating is prepared on the surface of the antenna cover by a dipping method and placed in an oven to be cured.

[0011] Preferably, the sandpaper can be one or more of 30-400 mesh diamond sandpaper, white corundum sandpaper, green carbon sandpaper.

[0012] Preferably, in step 1, the acid used in the pretreatment of the coated article is one or more of phosphoric acid, hydrochloric acid, sulfuric acid, and organic acid, which are diluted with a solvent for corrosion and roughening, and the acid concentration is 5%-50%, and the cleaning solvent is ethanol or acetone.

[0013] Preferably, in step 2, the polycarbosilane and the resin are modified, the resin is any one of an epoxy resin and a silicone resin, the modification treatment of the polycarbosilane is a hydrogenation treatment, the polycarbosilane is cross-linked using divinylbenzene as a cross-linking agent, and the epoxy resin and the silicone resin are coupled with a coupling agent, and the coupling agent is any one of a silane coupling agent and a titanate coupling agent.

[0014] Preferably, the stirring time for preparing the coating solution in step 3 is ≥10 min, and the amount of plasticizer and leveling agent added is 0.5%-2%.

[0015] Preferably, the inorganic filler in step 4 is one or more of glass fiber, quartz fiber, alumina fiber, carbon fiber, silicon carbide fiber, quartz powder, and zirconium oxide powder, and the added amount of the inorganic filler is 1%-5%.

[0016] Preferably, in step 4, the solvent is any one of xylene, toluene, acetone, and tetrahydrofuran, the mass ratio of divinylbenzene added as a crosslinking agent to polycarbosilane is 1: (0.2-1), the amount of xylene, toluene, acetone, and tetrahydrofuran added is 10%-100% of the mixed coating, and the ball milling time is 10min-60min.

[0017] Preferably, the immersion method in step 5 is to place the article to be coated in the mixed coating solution for 1-5 minutes, then take it out, scrape off the excess solution, place it in an oven, and dry it at 80°C for 5 minutes. During the drying process, slowly rotate the sample to avoid solution aggregation, and repeat 5-10 times.

[0018] Preferably, the curing process in step 5 is carried out in an environment of protective gas, heating to 60°C in 30-45 minutes, keeping warm for 1-2 hours, heating to 100°C in 30-45 minutes, keeping warm for 1-2 hours, heating to 150°C in 30-45 minutes, keeping warm for 1-2 hours, heating to 180°C in 30-45 minutes, and cooling with the furnace.

[0019] Preferably, the thickness of the composite coating obtained in step 5 is 0.2-3 mm.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the anti-laser ablation coating of the present invention has a simple preparation method and high bonding strength with the product, utilizes polycarbosilane to be converted into SiC at high temperature, and epoxy resin is ablated to absorb part of the heat of the laser, and the chopped fibers and inorganic fillers contained in the coating can play a heat insulation and protective effect, and the generated SiC and fillers can reflect lasers, so the coating has excellent anti-laser ablation performance, and can effectively protect the shells of engines, missiles, etc. from damage. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The experimental methods and instruments in the embodiments of the present invention are commercially available. Among the reagents used, the purity of the diluent is ≥99.5%; the purity of xylene is ≥99.0%;

[0023] Example 1

[0024] A method for preparing a polycarbosilane composite coating for a radar radome comprises the following steps:

[0025] Use 30-mesh diamond sandpaper to grind and roughen the product to be coated, then clean it with anhydrous ethanol and dry it;

[0026] Take 5g of polycarbosilane for hydrogenation treatment, then add 1g of divinylbenzene for crosslinking treatment, take 10g of epoxy resin, add 10g of silane coupling agent for coupling treatment;

[0027] 0.075 g of plasticizer and leveling agent were added to the modified polycarbosilane and epoxy resin, and the mixture was stirred on a magnetic stirrer for 10 min to prepare a coating solution;

[0028] 1.25 g of zirconium oxide powder, 0.25 g of alumina fiber and 2.5 g of xylene were added to the coating solution, and the mixture was stirred on a planetary ball mill for 10 min to obtain a mixed coating solution;

[0029] Immerse the product to be coated in the mixed coating solution for 5 minutes and take it out, scrape off the excess solution with a scraper, then place it in an oven at 80°C, slowly rotate the sample, take it out after 5 minutes, and repeat 5 times;

[0030] The sample coated with the coating solution was placed in a protective atmosphere tube furnace, heated to 60°C in 30 minutes, kept warm for 1 hour, heated to 100°C in 30 minutes, kept warm for 1 hour, heated to 150°C in 30 minutes, kept warm for 1 hour, heated to 180°C in 30 minutes, kept warm for 1 hour, cooled with the furnace, and the coating was obtained. The coating thickness was 1mm. The protective gas was nitrogen with a flow rate of 450ml / min.

[0031] Example 2

[0032] Use 400-grit green carbon sandpaper to roughen the product to be coated, then clean it with acetone and dry it;

[0033] Take 5g of polycarbosilane for hydrogenation treatment, then add 3g of divinylbenzene for crosslinking treatment, take 5g of epoxy resin, add 5g of phthalate coupling agent for coupling treatment;

[0034] 0.2 g of plasticizer and leveling agent were added to the modified polycarbosilane and epoxy resin, and the mixture was stirred on a magnetic stirrer for 30 min to prepare a coating solution;

[0035] 0.18 g of quartz powder, 1.0 g of quartz fiber and 9 g of tetrahydrofuran were added to the coating solution, and the mixture was stirred on a planetary ball mill for 60 min to obtain a mixed coating solution;

[0036] Immerse the product to be coated in the mixed coating solution for 5 minutes and take it out, scrape off the excess solution with a scraper, then place it in an oven at 80°C, slowly rotate the sample, take it out after 5 minutes, and repeat 10 times;

[0037] The sample coated with the coating solution was placed in a protective atmosphere tube furnace, heated to 60°C in 45 minutes, kept warm for 1 hour, heated to 100°C in 45 minutes, kept warm for 1 hour, heated to 150°C in 45 minutes, kept warm for 1 hour, heated to 180°C in 45 minutes, kept warm for 1 hour, cooled with the furnace, and the coating was obtained. The coating thickness was 2 mm. The protective gas was nitrogen with a flow rate of 450 ml / min.

[0038] Example 3

[0039] Use 5% phosphoric acid diluted with a solvent to corrode and roughen the product to be coated, then clean it with anhydrous ethanol and dry it;

[0040] Take 5g of polycarbosilane for hydrogenation treatment, then add 4g of divinylbenzene for crosslinking treatment, take 15g of silicone resin, add 0.50g of silane coupling agent for coupling treatment;

[0041] 0.2 g of plasticizer and leveling agent were added to the modified polycarbosilane and epoxy resin, and the mixture was stirred on a magnetic stirrer for 10 min to prepare a coating solution;

[0042] 0.24 g of zirconium oxide powder, 1.2 g of glass fiber and silicon carbide fiber, and 24 g of acetone were added to the coating solution, and the mixture was stirred on a planetary ball mill for 10 min to obtain a mixed coating solution;

[0043] Immerse the product to be coated in the mixed coating solution for 3 minutes and take it out, scrape off the excess solution with a scraper, then place it in an oven at 80°C, slowly rotate the sample, take it out after 5 minutes, and repeat 5 times;

[0044] The sample coated with the coating solution was placed in a protective atmosphere tube furnace, heated to 60°C in 45 minutes, kept warm for 1 hour, heated to 100°C in 45 minutes, kept warm for 1 hour, heated to 150°C in 45 minutes, kept warm for 1 hour, heated to 180°C in 45 minutes, kept warm for 1 hour, cooled with the furnace, and the coating was obtained. The coating thickness was 0.6 mm. The protective gas was nitrogen with a flow rate of 450 ml / min.

[0045] Example 4

[0046] Use 50% organic acid diluted with solvent to corrode and roughen the product to be coated, then clean it with acetone and dry it;

[0047] Take 5g of polycarbosilane for hydrogenation treatment, then add 2g of divinylbenzene for crosslinking treatment, take 20g of silicone resin, add 0.60g of phthalate coupling agent for coupling treatment;

[0048] 0.25 g of plasticizer and leveling agent were added to the modified polycarbosilane and epoxy resin, and the mixture was stirred on a magnetic stirrer for 60 min to prepare a coating solution;

[0049] 1.4 g of quartz powder and zirconium oxide, 0.27 g of carbon fiber and silicon carbide fiber, and 15 g of xylene were added to the coating solution, and the mixture was stirred on a planetary ball mill for 30 min to obtain a mixed coating solution;

[0050] Immerse the product to be coated in the mixed coating solution for 3 minutes and take it out, scrape off the excess solution with a scraper, then place it in an oven at 80°C, slowly rotate the sample, take it out after 5 minutes, and repeat 10 times;

[0051] The sample coated with the coating solution was placed in a protective atmosphere tube furnace, heated to 60°C in 45 minutes, kept warm for 2 hours, heated to 100°C in 45 minutes, kept warm for 2 hours, heated to 150°C in 45 minutes, kept warm for 2 hours, heated to 180°C in 45 minutes, kept warm for 2 hours, cooled with the furnace, and the coating was obtained. The coating thickness was 1.2 mm. The protective gas was nitrogen with a flow rate of 450 ml / min.

[0052] The coating prepared in Example 1 was ablated with an oxyacetylene flame at 1200° C. for 5 seconds. The back of the substrate did not change at all, but the ablated central area of ​​the coating surface was slightly carbonized and cracked.

[0053] The coating prepared in Example 2 was ablated with an oxyacetylene flame at 1800° C. for 5 seconds. There was no obvious change on the back of the substrate. The ablated central area of ​​the coating surface was severely carbonized, with many cracks, and the adhesion was reduced.

[0054] The coating prepared in Example 3 was ablated with an oxyacetylene flame at 1200° C. for 5 seconds. There was no obvious change on the back of the substrate. The ablated central area of ​​the coating surface was carbonized and blackened, and cracks appeared. However, the coating had good adhesion and was not easy to peel off.

[0055] The coating prepared in Example 4 was ablated with an oxyacetylene flame at 1800° C. for 5 seconds. The back of the substrate was slightly blackened, the central area of ​​the coating surface was severely carbonized, the coating peeled off, the coating in the peripheral area curled, and the coating adhesion was significantly reduced.

[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a polycarbosilane composite coating for a radar antenna cover, characterized in that: The steps include: Step 1: Pre-treat the product to be coated by roughening it with sandpaper or acid corrosion, then clean it with a cleaning solvent and put it in an oven for drying; Step 2: Modification of polycarbosilane and resin; Step 3: Add the modified polycarbosilane to the leveling agent and the plasticizer and stir evenly to prepare a coating solution; Step 4: Adding inorganic fillers and solvents to the coating solution to prepare a mixed coating by rapid ball milling; Step 5: A coating is prepared on the surface of the antenna cover by a dipping method and placed in an oven to be cured.

2. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: The sandpaper is one or more of 30-400 mesh diamond sandpaper, white corundum sandpaper, green carbon sandpaper.

3. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: Step 1: The acid used in the pretreatment of the product to be coated is one or more of phosphoric acid, hydrochloric acid, sulfuric acid, and organic acid, which are diluted with a solvent for corrosion and roughening. The acid concentration is 5%-50%, and the cleaning solvent is ethanol or acetone.

4. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: In step 2, the polycarbosilane and the resin are modified, the resin is any one of epoxy resin and silicone resin, the modification treatment of the polycarbosilane is hydrogenation treatment, the polycarbosilane uses divinylbenzene as a cross-linking agent for cross-linking reaction, the epoxy resin and the silicone resin are coupled with a coupling agent, and the coupling agent is any one of a silane coupling agent and a titanate coupling agent.

5. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: The stirring time for preparing the coating solution in step 3 is ≥10 min, and the amount of plasticizer and leveling agent added is 0.5%-2%.

6. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: In step 4, the inorganic filler is one or more of glass fiber, quartz fiber, alumina fiber, carbon fiber, silicon carbide fiber, quartz powder, and zirconium oxide powder, and the addition amount of the inorganic filler is 1%-5%.

7. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 4, characterized in that: In step 4, the solvent is any one of xylene, toluene, acetone, and tetrahydrofuran, the mass ratio of divinylbenzene added as a crosslinking agent to polycarbosilane is 1: (0.2-1), the amount of xylene, toluene, acetone, and tetrahydrofuran added is 10%-100% of the mixed coating, and the ball milling time is 10min-60min.

8. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: The immersion method in step 5 is to place the article to be coated in the mixed coating solution for 1-5 minutes, then take it out, scrape off the excess solution, place it in an oven, and dry it at 80°C for 5 minutes. During the drying process, slowly rotate the sample to avoid solution aggregation, and repeat 5-10 times.

9. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: In step 5, the curing process is carried out in an environment of protective gas. The temperature is raised to 60°C in 30-45 minutes, kept warm for 1-2 hours, raised to 100°C in 30-45 minutes, kept warm for 1-2 hours, raised to 150°C in 30-45 minutes, kept warm for 1-2 hours, raised to 180°C in 30-45 minutes, and cooled with the furnace.

10. The method for preparing a polycarbosilane composite coating for a radar antenna cover according to claim 1, characterized in that: The thickness of the composite coating obtained in step 5 is 0.2-3 mm.

Citation Information

Patent Citations

  • Protective coating layer for resisting laser ablation and preparation method thereof

    CN101445702A

  • Preparation method and application of low-cost liquid polycarbosilane

    CN113999397A

  • Resin composition and its production and molded product

    JP1999124436A

  • KR20220057256A

Cited By

  • Preparation method of anti-laser ablation coating based on C / C-SiC paper

    CN121827136A